Space War and the Regressive Development of the Principle of Common Heritage of Humankind: Legal vs. Technological Weapons - Nur Gemilang Mahardhika (Jurnal Hukum IUS QUIA IUSTUM, 2023)
Deep under the waters, HMS Challenger discovered the polymetallic nodules during its scientific expeditions in the Kara Sea part of the Arctic Ocean in 1868. Whilst in the vastness of the skies above, the Clementine and Lunar Prospector indicated the existence of water ice at the lunar poles during the period of 1994 to 1999. In 2003, the SMART-1 lunar orbiter of the European Space Agency discovered the key chemical elements of the Moon. Going even further back, in 1988, NASA published a work on Helium-3 blown away by the solar wind onto the Moon, and the possibilities of harvesting it as an alternative energy source for the continuation and advancement of human race. The deep seabed and the outer space, along with their resources, are both internationally governed under the same underlying principle: the Common Heritage of Humankind. Yet, while the former has begun to take shape, the latter still has very little progress. Various factors ranging from laws to politics to economics and undeniably the advances in science and technology have hindered the development of the principle of Common Heritage of Humankind in the outer space regime. Hence, this paper is to argue on how best to reform the principle, and consequently, determining which of its elements that might be spared in order for it to eventually work in balancing the contrasting interests from diverse stake-holders: the developed and the developing countries; the sovereign and the corporations – with their respective weapons of laws or of technology.Keywords: Common Heritage of Humankind; Outer Space Regime; Deep Seabed AbstrakJauh di dasar samudera, HMS Challenger menemukan polymetallic nodules dalam ekspedisi ilmiahnya di Laut Kara bagian dari Samudra Arktik pada tahun 1868. Sementara di ruang angkasa yang tak terbatas, Clementine dan Lunar Prospector menunjukkan adanya air es di kutub-kutub di Bulan dalam periode 1994 hingga 1999. Pada tahun 2003, pengorbit bulan SMART-1 dari Badan Antariksa Eropa menemukan unsur-unsur kimia utama Bulan. Lebih jauh ke belakang, pada tahun 1988, NASA menerbitkan sebuah karya tentang Helium-3 yang diterbangkan oleh angin matahari ke Bulan, dan kemungkinan memanennya sebagai sumber energi alternatif untuk kelanjutan dan kemajuan umat manusia. Dasar samudera dalam dan ruang angkasa, beserta seluruh kandungan sumber dayanya, secara internasional diatur berdasarkan prinsip fundamental yang sama: Common Heritage of Humankind. Namun, sementara pengaplikasian prinsip ini di rezim Hukum Laut mulai terbentuk, rezim Hukum Ruang Angkasa hanya memiliki sedikit kemajuan. Berbagai faktor mulai dari hukum hingga politik, ekonomi dan tidak dapat dipungkiri kemajuan ilmu pengetahuan dan teknologi telah menghambat perkembangan prinsip Common Heritage of Humankind di rezim ruang angkasa. Oleh karena itu, tulisan ini adalah untuk mendebat cara terbaik untuk mereformasi prinsip tersebut, dan menentukan elemen mana yang mungkin dapat dikorbankan agar pada akhirnya prinsip ini dapat benar-benar berlaku dengan cara yang dapat menyeimbangkan kepentingan yang berlawanan dari berbagai pemangku kepentingan: negara maju dan negara berkembang; pemerintah dan korporat – dengan senjata hukum atau ataupun senjata teknologi masing-masing. Kata-kata Kunci: Common Heritage of Humankind; Rezim Ruang Angkasa; Dasar Samudera Dalam